1994
DOI: 10.1152/jappl.1994.76.6.2765
|View full text |Cite
|
Sign up to set email alerts
|

Ventilatory variability induced by spontaneous variations of PaCO2 in humans

Abstract: We tested the hypothesis that breath-to-breath variations in arterial CO2 partial pressure (PaCO2) during spontaneous breathing of awake humans cause a significant portion of spontaneous ventilatory variability (including periodic oscillations). This hypothesis was tested in two ways. First, using a recently developed adaptive PaCO2 buffering technique we reduced the spontaneous variability in PaCO2 of six awake normal young human subjects during hyperoxia and observed a corresponding decrease in their breath-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
34
2

Year Published

1995
1995
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(39 citation statements)
references
References 0 publications
2
34
2
Order By: Relevance
“…In anesthetized, vagotomized spontaneously breathing rats, Khatib and associates (25) found that inhalation of 4070 carbon dioxide caused 3 of 3 animals to have positive correlations between the VTof one breath with that of the next, whereas VT was negatively correlated between adjoining breaths in 5 of 7 animals during air breathing. Additional evidence supporting the importance of chemoreceptor activity as a source of ventilatory variability is provided by recent data of Modarreszadeh and Bruce (33). They used a computer-controlled buffering technique to reduce spontaneous variability in arterial carbon dioxide tension, and observed a corresponding decrease in breath-to-breath variation in ventilation.…”
Section: Implications Concerning Respiratory Controlmentioning
confidence: 90%
“…In anesthetized, vagotomized spontaneously breathing rats, Khatib and associates (25) found that inhalation of 4070 carbon dioxide caused 3 of 3 animals to have positive correlations between the VTof one breath with that of the next, whereas VT was negatively correlated between adjoining breaths in 5 of 7 animals during air breathing. Additional evidence supporting the importance of chemoreceptor activity as a source of ventilatory variability is provided by recent data of Modarreszadeh and Bruce (33). They used a computer-controlled buffering technique to reduce spontaneous variability in arterial carbon dioxide tension, and observed a corresponding decrease in breath-to-breath variation in ventilation.…”
Section: Implications Concerning Respiratory Controlmentioning
confidence: 90%
“…Furthermore, these breathing-related fluctuations are particularly problematic for resting-state connectivity analyses, which rely on the correlation of time-series between brain regions to infer a functional connection. As demonstrated in previous studies, the fluctuations in breathing during rest generally occur at similar frequencies (~0.03 Hz) and in similar brain regions as those implicated in resting-state default-mode network activity (Birn et al, 2006;Modarreszadeh et al, 1994;Van den Aardweg et al, 2002;Wise et al, 2004). Therefore, in order to obtain resting-state activity maps that reflect fluctuations in neuronal activity exclusively, it is vital that these respiration-induced fluctuations are modeled or removed from the data.…”
Section: Introductionmentioning
confidence: 92%
“…Furthermore, several authors have employed system identification techniques based on autoregressive models that make use of the breath-to-breath dependence of ventilation on arterial blood gas tensions (via chemoreceptors) as well as dependence of O 2 /CO 2 on ventilation (due to gas exchange) (Khoo and Marmarelis, 1989; Mitsis et al, 2009; Nemati et al, 2011). Lastly, many researchers have used autoregressive modeling in the presence of exogenous stimulations (e.g., pseudorandom binary sequences of inhaled CO 2 ) in an attempt to estimate LG during sleep (Ghazanshahi and Khoo, 1997; Modarreszadeh and Bruce, 1994; Modarreszadeh et al, 1995). However, none of these techniques has emerged as a useful and reliable tool for noninvasively estimating LG, possibly because recordings of respiratory variables are noisy and non-stationary.…”
Section: Discussionmentioning
confidence: 99%